Sign language phonology - Brentari, Diane (Cambridge, United Kingdom Cambridge University Press, 2022)
"Key Topics in Phonology focuses on the main topics of study in phonology today. It consists of accessible yet challenging accounts of the most important issues, concepts and phenomena to consider when examining the sound structure of language. Some topics have been the subject of phonological study for many years and are re-examined in this series in light of new developments in the field; others are issues of growing importance that have not so far been given a sustained treatment"-- Provided by publisher.
Introduction: Sign language versus gesture: Sign language versus speech -- Modality effects -- Iconicity -- Interfaces -- The emergence of phonology -- Sign language phonological processing -- Sign language acquisition -- Sign language phonological variation and change.
Keywords: American Sign Language; Sign language; Grammar, Comparative and general -- Phonology